Pengukuran Kinerja Karyawan UD Akbar Jaya Bakery dengan Metode KPI dalam Meningkatkan Kapasitas Produksi - Zaharuddin, Zaharuddin; Roy D.T Sibarani; M. Fazri (SURYA TEKNIKA, 2024)
Performance measurement is one of the methods used to control the development of organizations and companies in order to maintain the company's competitiveness. UMKM Akbar Jaya Bakery is a company founded in 2001 located in the city of Medan which operates in the bread and cake industry with 8 employees. The problem in this research is the planned daily production capacity not being achieved which is caused by unstable employee performance in each production process. This research aims to optimize the level of performance measurement of Akbar Jaya Bakery employees in order to meet daily production targets using the KPI method. Key performance indicators are a management tool or instrument so that an activity or process carried out can be followed, controlled and ensured that it can achieve performance in accordance with what is desired by a company in order to meet production quality. Based on this research, only 4 indicators are the most prioritized in improving employee performance, namely efficiency in the use of raw materials with a yield value of 125%, human resources who have expertise with a yield value of 100%, additional production equipment 166%, and increasing types of cakes with a yield value of 200%.